2012
DOI: 10.2340/16501977-0971
|View full text |Cite
|
Sign up to set email alerts
|

Association between rehabilitation timing and major complications of total knee arthroplatsy

Abstract: The results of this study indicated that, because the incidence rates of complications and medical service utilization among total knee arthroplasty patients in the within 2 weeks group were lower than in the after 2 weeks group, the timing of rehabilitation may be 1 factor affecting post-TKA complications and promoting high levels of medical service utilization. These findings could be useful for clinicians and health policymakers attempting to improve total knee arthroplasty services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…Overall, reduced quality across studies can be attributed to inadequate reporting of blinding, loss to follow up, randomization, and adjustment for confounding variables in the analyses. Of the 17 studies included, 4 were randomized clinical trials, [32, 36, 43, 45] 1 was a quasi-experimental study, [33] 1 was a cost-effectiveness study, [34] based on the Larsen et al 2008 randomized clinical trial, [36] 6 were prospective cohort studies, [29, 35, 39, 40, 46, 47] and 5 were retrospective cohort studies [30, 31, 37, 38, 50]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, reduced quality across studies can be attributed to inadequate reporting of blinding, loss to follow up, randomization, and adjustment for confounding variables in the analyses. Of the 17 studies included, 4 were randomized clinical trials, [32, 36, 43, 45] 1 was a quasi-experimental study, [33] 1 was a cost-effectiveness study, [34] based on the Larsen et al 2008 randomized clinical trial, [36] 6 were prospective cohort studies, [29, 35, 39, 40, 46, 47] and 5 were retrospective cohort studies [30, 31, 37, 38, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…Costs, on the other hand, were defined differently among the included studies. Chen et al [30] defined total medical expenses as rehabilitation expenses related to rehabilitation services in the index visit, as well as outpatient and inpatient expenses related to prosthetic infection and deep vein thrombosis within one year after discharge. Larsen et al [34] defined total medical expenses as costs associated with the information day, hospital stay, care in the hospital, rehabilitation in the hospital, patient needs, primary care in the follow-up period, and hospital re-admission in the follow-up period of one year after discharge.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [5] reported that early rehabilitation after total knee arthroplasty (TKA) is associated with reducing major complications such as deep vein thrombosis (DVT) and prosthetic infection. Trampuz and Zimmerli [6] also found that prosthetic infection is associated with poor skin and soft-tissue healing, which is secondary to poor circulation that can be improved through rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…A complicação mais frequente na artroplastia de joelho é o tromboembolismo -aproximadamente 50% das artroplastias unilaterais e 75% das artroplastias bilaterais apresentarão esta complicação se não receberem nenhum tipo de profilaxia 7 . Outra complicação é a infecção, embora não seja a mais frequente, é a mais temida 8 .…”
unclassified
“…Outras complicações podem ser citadas como fratura por estresse ou trauma agudo, luxação ou subluxação femoropatelar, rigidez articular, lesão vascular, lesão nervosa, distúrbios da pele, dor e falha da artroplastia de joelho que envolve mecanismos como soltura, desgaste e erro na colocação da prótese 8,9 . O processo de reabilitação para a artroplastia de joelho pode incluir instruções para o paciente desde o pré-operatório, a fisioterapia terá um papel fundamental durante o pós-operatório, onde podemos ter três estágios do processo de reabilitação: Fase de proteção máxima (1 a 2 semanas), quando os objetivos são prevenir a inibição reflexa ou a perda de força muscular de joelho e quadril, recuperar a amplitude de movimento (90° para flexão e extensão completa) e controle do joelho, promover circulação, diminuir dor e edema, promover cicatrização da ferida cirúrgica, prevenir complicações respiratórias e vasculares; Fase de proteção moderada (três a seis semanas), quando os objetivos da fisioterapia são progredir a amplitude de movimento para 115° de flexão e 0° de extensão de joelho e aumentar a força e resistência muscular do membro inferior gradualmente; Fase de proteção mínima e retorno às atividades (à partir da sexta à 12º semana), quando os …”
unclassified